Antimicrobial activity of aqueous-alcoholic extracts from myrtle leaves in relation to strains isolated from patients with cystic fibrosis - V. D. Maslova; V. A. Kurkin; V. M. Ryzhov; A. V. Lyamin; O. V. Kondratenko; N. N. Bakova; E. Yu. Bakova (Фармация и фармакология (Пятигорск), 2025)
The search for new antimicrobial medicines based on medicinal plant raw materials (MPRM) and its effective and safe use in modern pharmaceutical practice remains one of the most pressing issues in pharmacy. Today, the search for new biologically active compounds (BACs) with antimicrobial and antifungal activity is ongoing. Due to the content of the BACs complex, preparations based on MPRMs have a milder effect on the human body compared to synthetic analogues. According to the results of studying some foreign studies and publications on the topic of antimicrobial and antifungal activity, a promising source of BACs, namely the leaves of common myrtle (Myrtus communis L.), is of scientific interest.The aim. Analysis and comparative study of the antibacterial activity of samples of extracts obtained using ethanol of various concentrations, and an infusion of common myrtle leaves (Myrtus communis L.) against clinical strains isolated from patients with cystic fibrosis.Materials and methods. The objects of the study were water-alcohol extracts from common myrtle leaves, comparison preparations — ethanol with a concentration of 40, 70, 96% and eucalyptus tincture. 5 strains of pathogenic microorganisms isolated from the sputum of patients with cystic fibrosis were used as test cultures. The minimum inhibitory concentration was assessed using the method of double serial dilutions in broth.Results. All water-alcohol extracts from common myrtle leaves showed antimicrobial activity exceeding the control samples against 3 mucoid strains — Burkholderia cenocepacia, Stenotrophomonas maltophilia and Pseudomonas aeruginosa. No antimicrobial activity was detected for the remaining 2 strains. A pronounced antimicrobial effect was possessed by 70% tincture and aqueous infusion of leaves.Conclusion. The data obtained during the study allow us to draw conclusions about the further prospects of studying 70% myrtle tincture and aqueous infusion for use in the therapy of patients with cystic fibrosis.